New Genotypes of Coxiella burnetii Circulating in Brazil and Argentina - Ribeiro Mioni, Mateus de Souza [UNESP]; Sidi-Boumedine, Karim; Dalanezi, Felipe Morales [UNESP]; Joaquim, Samea Fernandes [UNESP]; Denadai, Renan [UNESP]; Reis Teixeira, Wanderson Sirley [UNESP]; Labruna, Marcelo Bahia; Megid, Jane [UNESP] (Mdpi, 2020)
Coxiella burnetii, the zoonotic agent of Q fever, has a worldwide distribution. Despite the vast information about the circulating genotypes in Europe and North America, there is a lack of data regarding C. burnetii strains in South America. Here, we show the presence of novel multispacer sequence typing (MST) genotypes of C. burnetii in two clusters detected in Brazil and Argentina that seem to be distant in parenthood. Argentinian strains isolated from a tick belongs to a new phylogenetic branch of C. burnetii, and the Brazilians strains may be related to MST 20 and 61. Multilocus variable number tandem repeats analysis (MLVA) typing provided a deeper resolution that may be related to host clusters of bovines, caprine, ovine, and ticks. Our results corroborate with the reports of geotypes of C. burnetii. Thus, we highlight the need for more genotyping studies to understand the genetic diversity of C. burnetii in South America and to confirm the hypothesis of host-related genotypes. We also emphasize the importance of virulence studies for a better understanding of Q fever in the region, which may help in surveillance and disease prevention programs.
Keywords: Coxiella burnetii; Q fever; multilocus sequence typing (MST); tandem repeatsequences